Collective creativity between school and family. How migration backgrounds resonate between complex environments and communitarian times - Rosita Deluigi (Educazione Interculturale)
The educational alliances between school and family are conveyed by the mediation of collective subjects: school institutions and family units. If both are aimed at guaranteeing formative-educational opportunities for children and teenagers, they need times and spaces for co-constructing projects to support growth processes, logics of care and valorisation of different cultural heritages. The complexity that can emerge between school and family is made up of frames of reference that change over time, thanks to interaction in mutable contexts. The essay focuses on the need to understand the possibilities of dialogue between the pedagogical approaches of learning, experience and life environments. The reflection is set in a perspective of deconstructing the linearity of educational alliances, putting the experiential exchange between adults back at the centre, in the kid’s interest. The reflection will have as its backdrop projects implemented in pre-school and primary schools in which children’s creativity and curious discovery become a connective fabric between school and family. This will deepen the reflection on educational reciprocity towards a problematising dialogicity.